Changing Literacies for Changing Times : an Historical Perspective on the Future of Reading Research, Public Policy, and Classroom Practices. - James V. Hoffman (Taylor & Francis, 2009)
Offering the wisdom that only experience and expertise in the field can bring, this book takes a critical look into the present and the future of literacy as envisioned by leading reading researchers. The lead author of each chapter is a distinguished reading researcher elected by their peers into the Reading Hall of Fame. A key message in this book is that literacy professionals must take an active role to shape change.